Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1159/000454776
|View full text |Cite
|
Sign up to set email alerts
|

Specificities of Ischemic Stroke Risk Factors in Arab-Speaking Countries

Abstract: Background: Stroke is largely preventable, and therefore, a better understanding of risk factors is an essential step in reducing the population stroke rate and resulting disease burden in Arab countries. Summary: We performed 2 separate analyses in 2 similar populations of patients with noncardioembolic ischemic stroke. This first involved 3,635 patients in the Outcomes in Patients with TIA and Cerebrovascular disease (OPTIC) registry (followed for 2 years), with baseline collection of the usual risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
1
3
3
Order By: Relevance
“…The large, multinational OPTIC registry and PERFORM trial observed a trend of higher frequency of conventional risk factors for stroke, as well as inadequately managed diabetes mellitus, hypertension, and tobacco smoking in patients from Arab countries. 15 Though the significantly higher prevalence of diabetes mellitus among IS cases was noted in our study, diabetes mellitus and smoking were not found to be important risk factors on logistic regression analysis. Earlier studies have observed a younger age of occurrence of stroke in Arab countries.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The large, multinational OPTIC registry and PERFORM trial observed a trend of higher frequency of conventional risk factors for stroke, as well as inadequately managed diabetes mellitus, hypertension, and tobacco smoking in patients from Arab countries. 15 Though the significantly higher prevalence of diabetes mellitus among IS cases was noted in our study, diabetes mellitus and smoking were not found to be important risk factors on logistic regression analysis. Earlier studies have observed a younger age of occurrence of stroke in Arab countries.…”
Section: Discussioncontrasting
confidence: 60%
“…Earlier studies have observed a younger age of occurrence of stroke in Arab countries. 15 While 89% of the cases in the present study were in the age group above 45 years, the mean age of IS patients is at least a decade less than that reported in Western populations. A larger study may be required to provide a plausible explanation for these findings related to diabetes, smoking and older age in our cases in our study.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In men, MACEs occurred early: in the first year, the number of events was 87 (65.4%) and in the second year, 35 (26.3%) compared to 5 (3.7%) in the third, 3 (2.2%) in the fourth, and 3 (2.2%) in the fifth year. In women also, MACEs occurred predominantly in the first (63, 54.7%), second (28, 24.3%), and third (19,16.5%) years compared to the fourth (4, 3.4%) and fifth (1, 0.9%) years (Fig. 1).…”
Section: Maces During Follow-upmentioning
confidence: 93%
“…The reasons for these sexual difference may include decreased understanding of stroke in women [10], increase in incidence and poor management of risk factors [5,11], delays in admission to hospital [12], altered symptomatology leading to missing the diagnosis or delay in diagnosis [12,13], fewer investigations during the acute admission [13], less specialized care following admission [14], higher frequency of complications, and biological difference in endothelial and other functions in the 2 sexes [15]. Although a few studies from the Middle East have reported on the sexual differences in the risk factor profile [16], clinical presentation, and outcome of stroke [17], to our knowledge, there is no study reporting specifically on the effect of sexual difference in major adverse cardiovascular events (MACEs). We have previously reported on the risk factors, clinical presentation, and outcome following AS in a diverse group of patients in Qatar [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%